2020
DOI: 10.12968/nrec.2020.22.5.8
|View full text |Cite
|
Sign up to set email alerts
|

The power of song: music therapy and dementia

Abstract: Advanced or complex dementia requires a blend of treatment and therapy for effective management. Gloucestershire charity Mindsong explains its work in using music therapy to reduce stress and support daily care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
3
3
0
Order By: Relevance
“…Person-centred playlists not only enabled the reminiscence of family, places, love, and loss, but also became a means of encouragement for the residents to participate in physically and cognitively stimulating activities. We found, similar to other studies, an improvement in initiation and response of the RwADs, while the duration of the effectiveness varied among the studies [27,28,47]. While the effect of music is comparable with a low to medium effect size [46], the person-centred playlist based on each resident's preferences and cultural background and the residents' engagement by the musicians to the familiar songs and activities contributed to their connection to memory, reduced agitation, and functional improvements.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Person-centred playlists not only enabled the reminiscence of family, places, love, and loss, but also became a means of encouragement for the residents to participate in physically and cognitively stimulating activities. We found, similar to other studies, an improvement in initiation and response of the RwADs, while the duration of the effectiveness varied among the studies [27,28,47]. While the effect of music is comparable with a low to medium effect size [46], the person-centred playlist based on each resident's preferences and cultural background and the residents' engagement by the musicians to the familiar songs and activities contributed to their connection to memory, reduced agitation, and functional improvements.…”
Section: Discussionsupporting
confidence: 86%
“…Like in the current literature, this study's findings reported that the residents had an opportunity for memory connection, leading to a self-expression, because of the music [27,45,46]. The residents' memory connectedness was related to the tempo, dynamic, and style of the music, and their expressions (i.e., mumbling, touching, head turning, eye-contact, movement, and smiles) were the outcomes of memory connection [47]. Person-centred playlists not only enabled the reminiscence of family, places, love, and loss, but also became a means of encouragement for the residents to participate in physically and cognitively stimulating activities.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Musical imagination is one of the commonly used therapeutic methods in receptive music. Under the guidance of therapists, visitors imagine music, accompanied by corresponding situational music [ 23 , 24 ]. All the imaginary content is guided and controlled by the therapist.…”
Section: Statistical Data and Characteristic Analysis Of The Evaluati...mentioning
confidence: 99%
“…The 's memory connectedness was related to the tempo, dynamic, and style of the music; and their expressions [i.e. mumbling, touching, head turning, eyecontact, movement, and smiles] were the outcomes of memory connection (Grady & Beach, 2020). Person-centred playlist and playing musical instruments not only enabled the reminiscence of family, place, love, and loss, but also became a means of encouragement for the residents to show participate in physically and cognitively stimulating activities.…”
Section: Discussionmentioning
confidence: 99%